Effects of organic fertilizers produced from fish pond sediment on growth performances and yield of Malabar and Amaranthus vegetables - Dang Trung Thanh; Nguyen Minh Ty; Nguyen Vinh Hien; Håkan Berg; Thi Kieu Oanh Nguyen; Pham Thanh Vu; Vo Quang Minh; Chau Thi Da (Frontiers in Sustainable Food Systems, 2023)
The increasing intensification of aquaculture production requires the development of strategies to reduce its environmental impacts such as the pollution caused by the discharge of nutrient-rich sediments into local water bodies. This research was undertaken to investigate and evaluate the effect of using organic fertilizers produced from the pond sludge of freshwater snakehead fish (Channa striata) composted with organic amendments of peanut shells and coir fiber on growth performance indices and yields of Malabar spinach (Basella alba L.) and Amaranthus cruentus (Amaranthus L.) vegetables in the dry and wet seasons. An organic fertilizer quality experiment showed that the richest nutrient contents of the produced organic fertilizer were achieved when using 30% sludge mixed with 70% organic amendments (50% peanut shells + 50% coir fiber). This was selected and used for a vegetable cultivation experiment. For the reference treatment, only chemical fertilizer was applied, while in the other four treatments, 25, 50, 75, and 100% of the chemical fertilizer were substituted with the organic fertilizer. A 25–50% reduction in the chemical fertilizer application resulted in better growth performance indices and final yields than the other treatments, including the reference treatment, for both crops. The highest yields of Malabar spinach and Amaranthus cruentus vegetables were found in Treatment 3 (50% chemical fertilizer combined with 50% organic fertilizer), followed by Treatment 2 (25% organic fertilizer combined with 75% inorganic fertilizer) (P < 0.05). The results show that the reuse of sludge from snakehead fish ponds mixed with agricultural by-products as organic fertilizer for vegetables not only improves vegetable productivity but also reduces the costs of chemical fertilizer and decreases environmental pollution.